Revisiting the Central California Meganos Intrusion with New Stable Isotope and Radiocarbon Analyses at El Sobrante (CA-CCO-151). (2nd January 2020) - Eerkens, Jelmer W.; Bartelink, Eric J.
ABSTRACT: James Bennyhoff proposed a "Meganos intrusion" of people from the California Delta into the San Francisco Bay Area. Using new radiocarbon and stable isotope data, we re-examine stratigraphic and mortuary patterns at CA-CCO-151, the El Sobrante Mound. Which contains both a pre-Meganos (or Berkeley) and Meganos component. Results show that the transition to Meganos was gradual, occurring over a 200-year window between 1, 400 and 1, 210 cal B.P., with mortuary traits accumulating in piecemeal fashion. This is less consistent with an intrusion, and more in line with a slow diffusion of Meganos culture into the Bay Area. We propose a new model, wherein patrilocal Meganos populations had higher intrinsic growth rates than matrilocal Berkeley populations. Meganos males were able to marry into matrilocal Bay Area communities, and once there, passed on certain aspects of Meganos culture to their children. By virtue of higher Meganos out-migration, Bay Area communities slowly transitioned over roughly eight generations.